PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENGGUNAAN MODEL PROBLEM BASED INSTRUCTION KELAS VIII DI SMP SWASTA TAPIAN NAULI - Inggridt IC Yulia Tantri Purba; Roslian Lubis; Agus Saleh (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to improve students’ mathematical problem solving ability through using instruction based problem model on the topic of the Pythagorean theorem at the eighth grade students of SMP swasta Tapian Nauli. The research was conducted by applying Class Action Research (CAR) with 25 students as the subject. Instrument of the research was test, questionnaire, and observation. The research consists of two cycles. The first cycle showed (a) the test showed the students’ achievement of the Pythagorean theorem was 75.9, (b) observation sheet showed the average of students’ activities was 58.13, and (c) the observation of class teacher showed the ability of researcher in using instruction based problem model was 100.Furthermore, the second cycle showed (a) the test showed the students’ achievement of the Pythagorean theorem was 84.60, (b) observation sheet showed the average of students’ activities was 80.27, and (c) the observation of class teacher showed the ability of researcher in using instruction based problem model was 100. It’s concluded that instruction based problem model was able to improve students’ mathematical problem solving ability through using instruction based problem model on the topic of the Pythagorean theorem at the eighth grade students of SMP swasta Tapian Nauli.